2023
DOI: 10.1002/ohn.327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pneumococcal Vaccine on Otitis Media: A Systematic Review and Meta‐Analysis

Abstract: ObjectiveTo assess the effect of the pneumococcal vaccine (PCV) toward the surgical management and complications of otitis media.Data SourcesMEDLINE, EMBASE, PubMed, Scopus, and clinicaltrial.gov.Review MethodsA systematic search was performed using a combination of keywords and standardized terms about PCV and surgical management or complications of otitis media. Following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, studies were screened by 3 independent reviewers. Risk of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(212 reference statements)
1
1
0
Order By: Relevance
“…Indeed, we should also acknowledge that apart from vaccination, changes in environmental factors and socioeconomic disparities can also impact the variations in the burden of otitis media. Between the years 2010 and 2019, following the introduction of PHiD-CV and PCV-13, we observed a consistent reduction in the burden of otitis media aligning with previous research findings ( Izurieta et al 2022 ; Wannarong et al 2023 ). Nevertheless, this study identified an upward trend in the global incidence of otitis media from 2014 to 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we should also acknowledge that apart from vaccination, changes in environmental factors and socioeconomic disparities can also impact the variations in the burden of otitis media. Between the years 2010 and 2019, following the introduction of PHiD-CV and PCV-13, we observed a consistent reduction in the burden of otitis media aligning with previous research findings ( Izurieta et al 2022 ; Wannarong et al 2023 ). Nevertheless, this study identified an upward trend in the global incidence of otitis media from 2014 to 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Only 7 studies reported pneumococcal vaccination rates, so the impact of vaccination on the development of these outcomes was not assessed. However, recent studies have shown that while pneumococcal vaccines have decreased the number of AOM episodes, the number of otitis-prone children [ 76 ], and overall rates of invasive pneumococcal disease [ 77 , 78 ], the impact on acute mastoiditis is less clear, with one recent study showing an increase in acute mastoiditis by other Gram positive bacteria [ 79 ].…”
Section: Discussionmentioning
confidence: 99%